2012
DOI: 10.14712/18059694.2015.56
|View full text |Cite
|
Sign up to set email alerts
|

CD200/CD200R Paired Potent Inhibitory Molecules Regulating Immune and Inflammatory Responses; Part II : CD 200/CD200R Potential Clinical Applications

Abstract: CD200 and its receptor were recognized as having the multiple immunoregulatory functions. Their immunoregulatory, suppressive, and tolerogenic potentials could be very effectively exploited in the treatment of many diseases, e.g. Alzheimer disease, rheumatoid arthritis, and allergy to name only some. Many research projects are aimed to develop clinically valuable methods being based on the structure and function of these paired molecules. In this review, we would like to introduce CD200/CD200R functions in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…These two publications were landmark studies establishing the significance of CD200 and CD200R interactions as key regulators of inflammation in the brain. Since then, the field has grown significantly and has become specialized in studying the role of CD200 in a number of peripheral cell-mediated inflammatory and immune conditions, including arthritis 27,28], transplantation [29], viral infections [30,31], in the field of cancer [32,33] and also as a feature of neuroinflammation. CD200 is now known to be a significant player in cancer metastasis, with upregulation of CD200 being a negative factor as it promotes the evasion of cancer cells, including cancer stem cells, from the innate immune system [34].…”
Section: Biology Of Cd200 and The Cd200rmentioning
confidence: 99%
“…These two publications were landmark studies establishing the significance of CD200 and CD200R interactions as key regulators of inflammation in the brain. Since then, the field has grown significantly and has become specialized in studying the role of CD200 in a number of peripheral cell-mediated inflammatory and immune conditions, including arthritis 27,28], transplantation [29], viral infections [30,31], in the field of cancer [32,33] and also as a feature of neuroinflammation. CD200 is now known to be a significant player in cancer metastasis, with upregulation of CD200 being a negative factor as it promotes the evasion of cancer cells, including cancer stem cells, from the innate immune system [34].…”
Section: Biology Of Cd200 and The Cd200rmentioning
confidence: 99%
“…However, in addition to the inhibitory CD200R1, there is a series of activation receptors (CD200AR2, 3, 4, and 5) in mice (16). By using specific synthetic peptide ligands (CD200AR-L) that we identified through protein sequencing and structural analyses of CD200 (10), we developed a peptide-based strategy to engage these activation receptors on immune cells (10) and demonstrated that the inhibitory effects of CD200 protein can be surmounted by selectively engaging CD200ARs (11,17).…”
Section: Introductionmentioning
confidence: 99%
“…The ligand CD200, also a member of the IgSF, is widely expressed and therefore CD200R-CD200 interactions are involved in many immune-regulatory processes [156,158]. For instance, CD200R was found to attenuate inflammation in neurodegenerative and cardiovascular disorders, and also in allergy [159]. Pathogens and cancer cells may have evolved means that result in immune evasion: CD200 is up-regulated in leukemias and large DNA viruses including herpes-and poxviruses, seem to bind CD200 [159][160][161].…”
Section: Cd200rmentioning
confidence: 99%